KEBIJAKAN HUKUM PIDANA MATERIIL DI BIDANG PASAR MODAL - BAMBANG ALI KUSUMO (Wacana Hukum, 2009)
Abstract: The items regarded as crimes in stock market covers permition, deception, market manipulation and insider trading. The permition is that with least punishment among them while the most is deception, market manipulation and insider trading. Keyword: Policy, punishment